Wakaf Digital: Analisis Hukum Ekonomi Syariah, Akuntabilitas, dan Tata Kelola Nazhir - Purmini, Siti; Aulia, Rahma (TAWAZUN: Journal of Sharia Economic Law, 2026)
The development of digital technology has significantly transformed the practice of Islamic philanthropy, particularly in the management of waqf through digital platforms and Islamic financial technology. Digital waqf has emerged as an innovative model that facilitates the collection and distribution of waqf funds more effectively, efficiently, and inclusively. However, the implementation of digital waqf also raises several legal issues related to the validity of digital contracts, accountability of nazhir, and governance mechanisms in accordance with Islamic Economic Law principles. This study aims to analyze the validity of digital waqf from the perspective of Islamic Economic Law, examine the accountability of nazhir in managing digital waqf, and evaluate digital waqf governance based on maqāṣid syariah and Indonesian regulations. This research employs a normative juridical method with a qualitative descriptive-analytical approach through library research using primary, secondary, and tertiary legal materials. The findings reveal that digital waqf is legally permissible as long as it fulfills the pillars and conditions of waqf and complies with sharia principles such as transparency, mutual consent, and the absence of gharar and fraud. Furthermore, digital technology contributes to enhancing transparency and accountability in waqf management, although challenges remain regarding regulatory gaps, digital security, and human resource competence. Therefore, strengthening regulations, digital supervision systems, and professional governance standards are necessary to optimize sustainable digital waqf management in Indonesia.